HUBUNGAN ANTARA MOTIF BERPRESTASI DAN SIKAP SISWA TERHADAP PELAJARAN PENDIDIKAN LINGKUNGAN HIDUP DENGAN PRESTASI BELAJAR SISWAPADA PELAJARAN PENDIDIKAN LINGKUNGAN HIDUP - Retno Tri Andayani (IKIP Siliwangi Bandung, 2013)
This study aimed to obtain information about the relationship between achievement motives and attitudes towards learning of Environmental Education with student achievement in the subject of Environmental Education.The method used in this research is descriptive correlation method. The population in this study were students of class VII of SMP Negeri 1 Cimaragas Ciamis district, amounting to 176 people across 6 classes. The sampling technique used in this study is proportional random sampling technique, the sample size of 53 people. Instrument in this study using questionnaires and achievement motives questionnaire students' attitudes toward learning Environmental Education. While the data analysis techniques used are simple regression analysis and multiple regression analysis.The results showed variable achievement motive enough category, the variable students' attitudes toward learning for Environmental Education enough category and variables including student achievement in the subject of Environmental Education enough category. There is a relationship between achievement motive with student achievement in the subject of Environmental Education. This is evidenced by the acquisition value of the correlation coefficient of 0.680 which includes categories sufficient cohesion and contributes 46.2%. The better the achievement motive, the better student achievement in the subject of Environmental Education. There is a relationship between students' attitudes toward learning of Environmental Education with student achievement in the subject of Environmental Education. This is evidenced by the acquisition value of the correlation coefficient of 0.682 and a strong cohesion category contributed 46.5%. The better the students' attitudes toward environmental education lessons, the better student achievement in the subject of Environmental Education. There is a relationship between achievement motives and attitudes toward environmental education lessons with student achievement in the subject of Environmental Education. This is evidenced by the acquisition value of the correlation coefficient of 0.683 which is quite and closeness category contributed 46.6%. Getting better and better achievement motive students' attitudes toward environmental education lessons, the better student achievement in the subject of Environmental Education